The Effect of Prenatal Exercise and Effleurage Massage Techniques on the Perception of Back Pain in Third Trimester Pregnant Women - Rahayu Khairiah; Intan Maulida; Nisrina; Nana Nurdiana; Suminah; Sri Romdoningsih; Syifa Nurul S (Postgraduate, University of Mataram, 2024)
The perception of back pain is a common discomfort experienced by women in the third trimester of pregnancy. This pain occurs due to the release of the hormones progesterone and relaxin, which loosen the pelvic ligaments, and due to changes in body posture adapting to fetal development. The aim of this study is to analyze the effect of reducing pain before and after implementing prenatal exercises and effleurage massage in third-trimester pregnant women. This research used a quasi-experimental design with only one experimental group and no control group. The study population consisted of all third-trimester pregnant women experiencing back pain, with sampling conducted using accidental sampling. Data was collected using questionnaires and analyzed with the SPSS program, employing both univariate and bivariate tests. The results of the Paired Sample T-Test showed a significant difference between the pre-test and post-test values, with a significance value (2-tailed) of p = 0.000, < 0.05. The null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted, indicating a notable difference between the effects of prenatal exercise and effleurage massage before and after treatment in 180 third-trimester pregnant. There is a significant impact of prenatal exercise and effleurage massage on reducing back pain.